2015
DOI: 10.2152/jmi.62.248
|View full text |Cite
|
Sign up to set email alerts
|

Meralgia paresthetica caused by entrapment of the lateral femoral subcutaneous nerve at the fascia lata of the thigh: a case report and literature review

Abstract: Meralgia paresthetica (MP) causes tingling, stinging or a burning sensation in the anterolateral part of the thigh, usually as a result of entrapment of the lateral femoral cutaneous nerve (LFCN) at the inguinal ligament (IL) due to mechanical or iatrogenic injury. However, there are few reports on MP caused by entrapment of the LFCN at a more distal site from the IL. We report here a rare case of MP caused by entrapment of the LFCN at the fascia lata of the thigh level. A 23-year-old man felt numbness and sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Omichi et al () also reported a case of meralgia paresthetica caused by entrapment of the LFCN at the fascia lata level.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Omichi et al () also reported a case of meralgia paresthetica caused by entrapment of the LFCN at the fascia lata level.…”
Section: Resultsmentioning
confidence: 97%
“…This canal extends distally until the LFCN branches and pierces its walls toward the subcutaneous tissue. Omichi et al (2015) also reported a case of meralgia paresthetica caused by entrapment of the LFCN at the fascia lata level.…”
Section: Lower Extremity Entrapment Neuropathiesmentioning
confidence: 96%
“…Then LFCN pierces the deep fascia inferior to the inguinal ligament usually at a point about 2-3 cm distal to the ASIS. Then it runs laterally and distally within the subcutaneous tissue of the anterolateral aspect of the thigh where it is divided into two terminal braches (i.e., the anterior and posterior branches) [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This condition may also be caused by compression of the LFCN at the level of the inguinal ligament, and there are rare reports of MP after compression below the level of the inguinal ligament. 1 Neurophysiological investigations can be used to assess the integrity of the LFCN with both sensory nerve conduction studies and somatosensory evoked potentials described. Somatosensory evoked potentials have been reported to be both more sensitive than nerve conduction studies (81.3% vs 65.2%) and are better tolerated.…”
mentioning
confidence: 99%
“…Common causes of MP include mechanical pressure exerted on the LFCN, including prone positioning during surgery, obesity (body mass index [calculated as weight in kilograms divided by height in meters squared] >30), pregnancy, and the wearing of tight clothing, military uniforms, or lumbar braces. This condition may also be caused by compression of the LFCN at the level of the inguinal ligament, and there are rare reports of MP after compression below the level of the inguinal ligament …”
mentioning
confidence: 99%